Efficacy of azithromycin in severe asthma from the AMAZES randomised trial - Peter G. Gibson; Ian A. Yang; John W. Upham; Paul N. Reynolds; Sandra Hodge; Alan L. James; Christine Jenkins; Matthew Peters; Guy B. Marks; Melissa Baraket; Heather Powell; Jodie L. Simpson (2019)
Low-dose azithromycin is an effective therapy for persistent asthma; however, its benefit in severe asthma is not defined.Participants with severe asthma were identified from the AMAZES randomised, placebo-controlled trial of long-term (48 weeks) low-dose azithromycin. Participants who met one of the following severe asthma definitions were included: 1) Global Initiative for Asthma step 4 treatment with poor asthma control (asthma control questionnaire score ≥0.75); 2) International Severe Asthma Registry definition; 3) American Thoracic Society and European Respiratory Society severe asthma definitions. The rate of total exacerbations was calculated for each subgroup and efficacy of azithromycin compared with placebo. Asthma-related quality of life was assessed before and after treatment along with adverse effects.Azithromycin significantly reduced asthma exacerbations in each group. In patients meeting the American Thoracic Society and European Respiratory Society task force definition of severe asthma (n=211), the rate of exacerbations with treatment was 1.2 per person-year, which was significantly less than for placebo (2.01 per person-year), giving an incidence rate ratio (95% CI) of 0.63 (0.41, 0.96). The proportion of participants experiencing at least one asthma exacerbation was reduced by azithromycin from 64% to 49% (p=0.021). A similar beneficial treatment effect was seen in participants poorly controlled with Global Initiative for Asthma step 4 treatment and those with International Severe Asthma Registry-defined severe asthma. Azithromycin also significantly improved the quality of life in severe asthma (p<0.05). Treatment was well tolerated, with gastrointestinal symptoms being the main adverse effect.Long-term, low-dose azithromycin reduced asthma exacerbations and improved the quality of life in patients with severe asthma, regardless of how this was defined. These data support the addition of azithromycin as a treatment option for patients with severe asthma.